Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijerph17093292
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of a Dual-Channel Pharmaceutical Supply Chain Based on the Susceptible-Infected-Susceptible Epidemic Model

Abstract: With the continuous development of Internet, online pharmaceutical channels in many countries have seen rapid expansion. As a result, pharmaceutical supply chain participants can adopt dual channels, namely, both online channels and offline channels. As online channels compete with traditional offline channels, it is of great relevance to study the potential conflicts and coordination between them, which is the focus of this paper. Specifically, this article develops a susceptible-infected-susceptible epidemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…The effects of power relationships on the firm's decision-making, operation and performance have been extensively explored by scholars. Manufacturer Stackelberg, Retailer Stackelberg and Nash game models are established to investigate the influence of power structures on pricing and profit of the supply chain from the perspective of competition [20][21][22][23][24][25]. Some scholars indicated that whether a company benefits from its power force is related to the demand function and product differentiation [23][24][25].…”
Section: Power Structure In the Supply Chainmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of power relationships on the firm's decision-making, operation and performance have been extensively explored by scholars. Manufacturer Stackelberg, Retailer Stackelberg and Nash game models are established to investigate the influence of power structures on pricing and profit of the supply chain from the perspective of competition [20][21][22][23][24][25]. Some scholars indicated that whether a company benefits from its power force is related to the demand function and product differentiation [23][24][25].…”
Section: Power Structure In the Supply Chainmentioning
confidence: 99%
“…Some scholars indicated that whether a company benefits from its power force is related to the demand function and product differentiation [23][24][25]. Chen and Wang found that the smartphone supply chain should choose a bundled channel in Stackelberg power structures under certain conditions and select a free channel in a Nash power structure [21]. Most previous studies indicate that more power over other supply chain members enables manufacturers or retailers to obtain more profits.…”
Section: Power Structure In the Supply Chainmentioning
confidence: 99%
See 1 more Smart Citation